Effectiveness of influenza vaccination in reducing influenza-like illness and related antibiotic prescriptions in adults from a primary care-based case-control study. Issue 6 (December 2022) - He, Wen-Qiang; Gianacas, Christopher; Muscatello, David J; Newall, Anthony T; McIntyre, Peter; Cheng, Allen C; Liu, Bette
Highlights: Influenza vaccination reduced primary care presentations for ILI. The pooled estimated reduction over 4 years was 24% (95%CI 11-34%). Influenza vaccination also reduced antibiotic prescribing for ILI. However, this was only observed in patients without comorbidities and aged 40-65yrs. Abstract: Background: Evidence on the effectiveness of influenza vaccine in preventing antibiotic prescriptions for influenza-like illness (ILI) in adults is limited. Methods: A primary care-based case-control study was conducted to estimate influenza vaccine effectiveness (VE) against influenza-like illness (ILI) and antibiotic prescribing for ILI in adults aged ≥40 years. Cases were patients diagnosed with ILI from 1 st June to 30 th September in each year, 2015-2018; a subset of those with ILI prescribed antibiotics was also defined. Controls were patients attending a practice who did not receive an ILI diagnosis. Generalised estimating equations were used to calculate adjusted VE overall, by age (<65 versus ≥65 years) and comorbidity status. Results: The number of ILI cases varied from 558 in 2018 to 2901 in 2017 and controls from 86618 in 2015 to 136763 in 2017. Over 4 years the pooled estimate of VE was 24% (95%CI, 11% to 34%) against ILI and 15% (95%CI, -3% to 29%) against antibiotic prescription for ILI. Influenza vaccine was effective in reducing ILI with an associated antibiotic prescriptions in patients aged <65 years (VE=23%, 95%CI, 3% to 38%) and if no comorbidities were recorded (VE=22%, 95%CI, 1% to 39%) but not in other subgroups. Conclusions: Influenza vaccine reduced the likelihood of antibiotic prescriptions for ILI in low-risk adults (40-64 years and those without comorbidities).